(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
In this paper we apply the Balance Sheet Approach to the economic analysis of the household sector. We produce the households’ balance sheets derived from the 2002, 2005 and 2008 Banco de España’s Survey of House hold Finances. The methodology applied yields relevant insights such as observing that the net wealth ofthe top 1% of the Spanish population increased from 7.6 to 19.1 million Euros perfamily. The Balance Sheet Approach confirms that wealth distribution mechanisms provoke an increase in economic inequality